Effects of isotope and chemical incoherence on self-diffusion of atoms in liquid alloys of gallium with isotopes of nickel: Experiments based on quasielastic neutron scattering versus molecular dynamics simulations - Goychuk, Igor; Panchenko, Artem; Shahzad, Anjum; Fauser, Steffen; Neiß, Christian; Götz, Klaus; Vogel, Carola; Weißer, Matthias; Hakim, Bishoy; Embs, Jan Peter; Englhard, Jonas; Bachmann, Julien; et al. (Physical Review B, 2025)
Quasielastic neutron scattering (QENS) is a powerful experimental technique to investigate the diffusion of atoms in liquids. It relies on the fact that at low 𝑄 values essentially only incoherent scattering is observed from the diffusing atoms. In the case of alloys composed of two chemical elements, it is commonly believed that at low 𝑄 QENS mainly probes the self-diffusion of the element with a nonzero incoherent scattering cross-section, while the element with a zero incoherent scattering cross-section does not contribute. However, the findings of this study challenge this belief. The study examines alloys of natural gallium (which has a nonzero incoherent scattering cross-section) and isotopes 58 Ni and 60 Ni (both of which have a zero incoherent scattering cross-section). A crucial factor to consider here is chemical incoherence, which typically leads to the renormalization of the incoherent cross-sections of different chemical elements within a mixture. Unfortunately, this renormalization is often disregarded in an ad hoc manner. Significantly, the alloy containing 58 Ni shows a notable renormalization, scattering incoherently to a similar degree as natural nickel in a comparable alloy with equivalent concentrations of chemical elements. Similarly perplexing, natural nickel scatters with great intensity despite being predominantly composed of 58 Ni and 60 Ni (around 94% of the total). This behavior can be attributed to the accepted phenomenon of isotope incoherence. We calculate the integral diffusion coefficients of Ga and Ni atoms in various liquid alloys from QENS experiments. These values are then compared to the results obtained from corresponding molecular dynamics simulations conducted at various temperatures, taking into account chemical incoherence. The comparison shows good agreement within the range of errors for the Ga1−𝑥⁢ 58Ni𝑥 alloy at two concentrations (𝑥=0.02 and 𝑥=0.1). The agreement also partially holds for the Ga1−𝑥⁢Ni𝑥 alloy with natural nickel and for the Ga1−𝑥⁢ 60Ni𝑥 alloy, despite certain difficulties discusse
CRIS-Team Scopus Importer:2025-02-17
Keywords: Diffusion; Alloys; Liquid metals; Ab initio molecular dynamics; Molecular dynamics; Neutron scattering

Specifications for Electronic Laboratory Notebooks (ELN) in the Photon and Neutron Community - Jordt, P.; Osterhoff, M.; Tymoshenko, Y.; Hakim, Bishoy; Dolcet, P.; Maurer, F.; Biniyaminov, V.; Amelung, L.; Dall’Antonia, F.; Grunwaldt, J. D.; Weber, F.; Lohstroh, W.; et al. (Synchrotron Radiation News, 2024)
CRIS-Team Scopus Importer:2025-04-01